Cell Neurobiology Techniques - Boulton, Alan A.; Baker, Glen B.; Bateson, Alan N.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1999)
Cell Neurobiology Techniques is the second work updating and expanding the best-selling inaugural volume of Humana Press's warmly received Neuromethods series, General Neurochemical Techniques (vol. 1). The cutting-edge techniques detailed in this new edition include those that are particularly popular in multidisciplinary neuroscience research. There are readily reproducible methods for establishing neural cell cultures, measuring enzymes and their inhibitors, and using quantitative autoradiography to study monoamine uptake sites and receptors in the brain. Additional methods cover the use of flow cytometry to study developmental neurobiology, applications of magnetic resonance spectroscopy (MRS) to human brain metabolism, and the study of drug metabolism. The companion volumes, In Vivo Neuromethods and In Vitro Neurochemical Techniques, review both in vivo methods and in vitro neurochemical and molecular neurobiological approaches. Like the original, all three cutting-edge works will prove exceptionally useful to those basic and clinical neuroscientists who want to expand the range of their current research or develop competence in complementary methods.
Quantitative Autoradiography of Monoamine Uptake Sites and Receptors in Rat and Mouse Brain -- Neural Cell Culture Techniques -- Neural Cell Adhesion Molecules -- On the Measurement of Enzymes and their Inhibitors -- Cytochrome P-450 Enzymes -- c-fos Expression as a Marker of Functional Activity in the Brain -- Immediate-Early Genes as Activity Markers in the CNS -- Principles of Drug Metabolism, with an Emphasis on Psychiatric Drugs -- Flow Cytometric Strategies to Study CNS Development -- Neurochemistry of Human Postmortem Brain -- Applications of Proton MRS to Study Human Brain Metabolism.
Keywords: Neurosciences; Neurosciences